157k views
2 votes
4×((-1+2-3+4-5+6-7...+1000)

2 Answers

6 votes

-1 + 2 - 3 + 4 - 5 + 6 - … - 999 + 1000

= -(1 + 3 + 5 + … + 999) + (2 + 4 + 6 + … + 1000)

= -((2 - 1) + (4 - 1) + (6 - 1) + … + (1000 - 1)) + 2 (1 + 2 + 3 + … + 500)

= -((2 + 4 + 6 + … + 1000) - 500) + 2 (1 + 2 + 3 + … + 500)

= -(2 (1 + 2 + 3 + … + 500) - 500) + 2 (1 + 2 + 3 + … + 500)

Let S = 1 + 2 + 3 + … + 500. Then this sum is equal to

= -(2S - 500) + 2S

= -2S + 500 + 2S

= 500

and multiplying by 4 gives 2000.

User Bloodyaugust
by
5.2k points
2 votes

Answer:


4* \left(\left(-1+2-3+4-5+6-7+1000\right)\right)


calculate\: within \: the \:parentheses


-1+2=1


=1-3+4-5+6-7+1000


1-3=-2


=-2+4-5+6-7+1000


-2+4=2


=-3+6-7+1000


3-7+1000


=-4+1000


=996


Multiply:-


4*996


=3984

--------------------------

Hope it helps..

Have a great day!!

User Adamfinstorp
by
4.5k points